PENGEMBANGAN BAHAN AJAR MENULIS PUISI DESKRIPSI WISATA PULAU MANDANGIN BERTAJUK MENGENAL ALAM MADURA DAN MENIKMATINYA MELALUI MENULIS SAJAK - Syarifudin, Albitar Septian; Farahiba , Ayyu Subhi (Hasta Wiyata, 2024)
Education is one of the efforts to preserve local wisdom through academic studies of the potentials of each region. Through education, all forms of potential such as culture and tourism will be studied, discussed and published by educational actors, namely teachers and students. Culture and tourism potential will be developed and published in various ways according to the competence of teachers taught to students. In this study, the competency of strengthening regional culture and tourism will be packaged in the development of teaching materials for writing poetry based on edutourism on Mandangin Island, Sampang, Madura, using the meaning net technique. This teaching material consists of poetry writing materials and descriptions of tourism potential on Mandangin Island, Sampang, Madura, which are packaged with infographic concepts. It is hoped that with this teaching material students will become dissemination agents and observers of tourism potentials, especially on Mandangin Island, Sampang Madura, so that contextual learning or meaningful learning will be created. Therefore, the development of teaching materials is important to provide education in the field of tourism through learning to write descriptive poetry.